2018
DOI: 10.1002/ecs2.2405
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection and movement of male moose in response to varying levels of off‐road vehicle access

Abstract: Many rural communities are increasingly relying on off‐road motorized vehicles to access wildlife for both subsistence harvest and recreational hunting. Understanding the effects of trail and road networks on wildlife behavior is crucial to effective management for subsistence opportunities in communities that depend on accessible populations as an ecosystem service. We collared 26 adult male moose (Alces alces) in interior Alaska to monitor fine‐scale habitat selection and movement patterns before, during, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…During our study (2012-2016), 4.8% (n = 5) of collared moose mortalities were from human harvest. Other studies found ungulates used habitats providing cover during the hunting season (Bjørneraas et al 2011, Bonnot et al 2013, Brown et al 2018; however, we did not explicitly observe that behavior. Contrary to our prediction, moose selected for areas closer to roads in winter and spring.…”
Section: Habitat Selectioncontrasting
confidence: 70%
See 1 more Smart Citation
“…During our study (2012-2016), 4.8% (n = 5) of collared moose mortalities were from human harvest. Other studies found ungulates used habitats providing cover during the hunting season (Bjørneraas et al 2011, Bonnot et al 2013, Brown et al 2018; however, we did not explicitly observe that behavior. Contrary to our prediction, moose selected for areas closer to roads in winter and spring.…”
Section: Habitat Selectioncontrasting
confidence: 70%
“…Female moose behave similarly in the fall, by avoiding roads yet using habitat with increased forage availability (i.e., wetlands, cutblocks). Brown et al (2018) reported that during the hunting season in Alaska, hunter access from trails and roads affected male moose movement and habitat selection to avoid risk. Although licensed harvest is predominately focused on male moose in our study area, we anticipate female moose to behave similarly in the fall because of the risk of mortality from subsistence harvest.…”
Section: Habitat Selectionmentioning
confidence: 99%
“…To quantify the phenology of changes in elk behavior associated with exposure to human hunters, we modeled the speed of elk movements (m/30 min) using quantile regression (Cribari-Neto and Zeileis 2010). We chose movement rates as our first focal metric because in ungulates it is more sensitive than resource selection as an indicator of behavioral change in response to hunting pressure (i.e., animals may be displaced without changing their resource selection behavior, but animals that change their resource selection must necessarily alter their spatial distribution; Brown et al 2018). This approach allowed us to quantify changes in the magnitude and variation of elk movements across hunt periods and treatments.…”
Section: Durationmentioning
confidence: 99%
“…Habitat selection using mixed-effect models can also be inferred at the population level (marginal inference) as well as the group or individual level (conditional inference; Muff et al 2016). We used a point-based approach in step selection modeling opposed to a path-based approach (Boyce et al 2003) and paired each hourly use point with five random steps (Thurfjell et al 2014, Brown et al 2018) starting from the same point of origin. We generated random step points by sampling from the observed distributions of step length and relative turning angle.…”
Section: Analysis Of Habitat Selectionmentioning
confidence: 99%